2016
DOI: 10.3390/su8101063
|View full text |Cite
|
Sign up to set email alerts
|

A Bottom-Up Building Stock Model for Tracking Regional Energy Targets—A Case Study of Kočevje

Abstract: Abstract:The paper addresses the development of a bottom-up building stock energy model (BuilS) for identification of the building stock renovation potential by considering energy performance of individual buildings through cross-linked data from various public available databases. The model enables integration of various EE and RES measures on the building stock to demonstrate long-term economic and environmental effects of different building stock refurbishment strategies. In the presented case study, the Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Dynamic simulation is used in determining construction properties, occupant comfort, HVAC system energy demands, energy conservation techniques etc. [2][3][4][5][6]. In one of our previous researches we used multi-criteria optimization methodology to determine an optimal energy retrofit solution in case of adequate envelope glazing selection [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dynamic simulation is used in determining construction properties, occupant comfort, HVAC system energy demands, energy conservation techniques etc. [2][3][4][5][6]. In one of our previous researches we used multi-criteria optimization methodology to determine an optimal energy retrofit solution in case of adequate envelope glazing selection [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, identifying the most appropriate combination of retrofit solutions required to meet targets can be extremely complex [8]. Many studies have been undertaken to provide methodologies to support the selection of appropriate retrofit solutions for domestic properties [9][10][11][12][13] but in practice it is proving difficult to implement these on a scale that will achieve the targets set due to the large number of barriers. Properties constructed during different time periods pose different retrofit challenges due to the materials available, construction methods and needs of the population at the time of construction and this is also true for dwelling in different locations.…”
Section: Million Tonnesmentioning
confidence: 99%
“…The building sector is a major contributor to energy consumption, accounting for around 20% of total energy consumption in China [1] and 40% in the U.S. and the U.K [2,3]. With the trend of facilitating sustainable development globally, building energy efficiency has been recognized as a critical issue in many countries and regions [4][5][6]. In China, it is reported that buildings are of great potential to contribute up to 50% energy saving [7], and more and more building energy efficiency policies have been and will be implemented to promote a sustainable environment [8].…”
Section: Introductionmentioning
confidence: 99%
“…Little attention has been paid to geospatial patterns of building energy consumption from a regional perspective, e.g., investigation of the factors impacting regional building energy consumption. As a result, the revealed relationships between influential features and energy consumption or suggestions to improve energy efficiency are more applicable to the building-level intervention but less to the regional level, which is essential to optimal policymaking and better city planning [6,16,19]. Regional building energy models help understand the relationships between potential influential features and regional or city level energy consumption [20], resulting in generating a more holistic view to inform policy formulation.…”
Section: Introductionmentioning
confidence: 99%